Editor's Choice – Pharmaceutical Management of Small Abdominal Aortic Aneurysms: A Systematic Review of the Clinical Evidence. Issue 6 (December 2015) - Kokje, V.B.C.; Hamming, J.F.; Lindeman, J.H.N.
Abstract : Background: Management of abdominal aortic aneurysms (AAAs) relies on surgical repair of larger AAAs. Consequently medical interventions inhibiting AAA progression could greatly reduce the need for surgical repair. A spectrum of pharmaceutical strategies has been reported, albeit conclusions often appear contradictory. Given the longstanding interest in pharmaceutical AAA stabilization, a systematic review of the available literature is relevant. Objectives: The aim is to provide an up to date systematic review of the available data on pharmaceutical therapies for stabilizing or impeding AAA growth. Methods: A search using Pubmed, Embase, Web of science, Cochrane, CINAHL, Academic Search Premier, and Science Direct identified 27 eligible papers that studied the clinical effect of the pharmaceutical therapy on AAA diameter growth. Results: This review shows that there is currently no pharmaceutical strategy that reduces AAA growth. Most studies are of poor methodological quality. Initial promising reports are often not confirmed in subsequent larger studies, raising the possibility of selective reporting. Conclusion: There is currently no pharmaceutical means that halts AAA growth.